Artificial Intelligence's impact on social entrepreneurship / Noorain Mohd Nordin - Mohd Nordin, Noorain (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial intelligence (AI) has brought about transformative changes in various industries, revolutionizing businesses with automation, predictive analytics, and enhanced optimization. The realm of social entrepreneurship is not exempt from AI's influence, as it is rapidly embracing this technology. In this article, we will delve into the impact of artificial intelligence on social entrepreneurship and how it is reshaping the sector. To begin, it is essential to grasp the essence of social entrepreneurship. It involves leveraging business principles and strategies to address social and environmental issues, aiming to create a positive impact on society while generating sustainable revenue for business growth. Social entrepreneurs demonstrate creativity by devising innovative solutions to address the needs of marginalized communities. Notable examples of social enterprises include TOMS shoes, which donates a pair of shoes to a child in need for every pair sold, and Warby Parker, providing affordable eyewear to those in need. AI is increasingly becoming a cornerstone of social entrepreneurship, fostering improvements in efficiency, scalability, and overall impact. Data analysis is one area where AI's profound impact is felt. Social entrepreneurs often operate in complex environments with limited resources, and AI proves instrumental in analyzing vast datasets to uncover trends and patterns. For instance, social enterprises working in healthcare can utilize AI to A scrutinize medical records, identifying patterns in disease outbreaks or gauging the effectiveness of various treatment options. This data-driven approach empowers social entrepreneurs to make more informed decisions and allocate resources more efficiently. Moreover, predictive analytics is another significant domain where AI is making its mark in social entrepreneurship. By harnessing machine learning algorithms, predictive analytics detects patterns in data, enabling accurate predictions about future events. This capability is particularly valuable for social enterprises involved in disaster response or humanitarian aid. For example, AI can forecast the likelihood of a natural disaster occurring in a specific region, thereby allowing social entrepreneurs to prepare and respond proactively and effectively